The 4G4G Genotype of the Plasminogen Activator Inhibitor 4G/5G Gene Polymorphism Is Associated with Coronary Atherosclerosis in Patients at High Risk for this Disease - Gardemann, Andreas; Lohre, Jana; Katz, Norbert; Tillmanns, Harald; Hehrlein, Friedrich Wilhelm; Haberbosch, Werner (Thrombosis and Haemostasis, 1999)
Background. Disturbances in fibrinolytic activity, such as increase in plasminogen activator inhibitor (PAI) activity, have been linked with an increased risk for coronary artery disease (CAD) and myocardial infarction (MI). Since 4G4G homozygotes of an insertion/deletion (4G/5G) gene variation in the promoter of PAI-I have been shown to have increased levels of PAI-I, we analysed the relation of this gene polymorphism to CAD and MI in a population of 2565 participants who underwent coronary angiography for diagnostic purposes.Results. In the total sample, the PAI-I 4G/4G genotype was associated with the presence, but not with the extent of CAD. However, in a subgroup of former and present smokers (n = 1782) or of individuals with a BMI above the mean value of 26.9 kg × m-2 (n = 1269), the PAI-I 4G4G genotype was not only associated with the presence, but also with the extent of CAD, defined either by the number of diseased vessels or by the CHD score according to Gensini. This observation also applied to other high-risk groups of individuals with high BMI and hypertension (n = 869), of subjects with high fibrinogen plasma levels (> 3.53 g × 1-1, mean value) and hypertension (n = 599) and of former and present smokers with high fibrinogen and hypertension (n = 452). An association of the gene variation with MI was not detected.Conclusions. The present data indicate that the 4G/4G genotype of the PAI-I gene polymorphism is an independent risk factor for coronary artery disease and that the additional presence of major cardiovascular risk factors accelerates the risk for this disease.